2020
DOI: 10.1200/jco.2020.38.29_suppl.141
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying treatment preferences and their association with financial toxicity in women with breast cancer.

Abstract: 141 Background: This study sought to understand treatment preferences and their association with financial toxicity in breast cancer patients served by Patient Advocate Foundation (PAF). Methods: This cross-sectional study used survey data from a nationwide sample of women with breast cancer who received assistance from PAF. Choice-based conjoint analysis elicited patient preferences and trade-offs. Latent class analysis segmented respondents into distinct preference groups. The Comprehensive Score for Financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In another study and not surprisingly, Chebli et al found that immediately after diagnosis, patients prioritized survival over financial concerns [47]. Variation in preferences is further supported by work with breast cancer patients that showed two distinct archetypes of patient preferences: those most concerned about affordability ('cost prioritizing') and those most preoccupied with their ability to work and interference with life events ('functional independenceprioritizing') [48]. Preferences may differ across different patient populations.…”
Section: Patient Cost Preferences and Values In Cancer Carementioning
confidence: 97%
“…In another study and not surprisingly, Chebli et al found that immediately after diagnosis, patients prioritized survival over financial concerns [47]. Variation in preferences is further supported by work with breast cancer patients that showed two distinct archetypes of patient preferences: those most concerned about affordability ('cost prioritizing') and those most preoccupied with their ability to work and interference with life events ('functional independenceprioritizing') [48]. Preferences may differ across different patient populations.…”
Section: Patient Cost Preferences and Values In Cancer Carementioning
confidence: 97%